Meningkatkan Keterampilan Berbicara Siswa Melalui Metode Sosiodrama Kelas V SD Negeri 0501 Hutanopan - Irma Sari Daulay; Nurhayati Siregar; Nur Uba Risky Hsb (Student Research Journal, 2023)
This research aims to determine the improvement in speaking skills of fifth grade students at SD Negeri 0501 Hutanopan using the sociodrama method. The type of research used is Classroom Action Research which consists of 2 cycles, each cycle consisting of planning, implementation, observation and reflection. This research was carried out in class V of SD Negeri 0501 Hutanopan. The data sources in this research were divided into two, namely (1) primary data, namely students of class V of SD Negeri 0501 Hutanopan, (2) secondary data, namely teachers of class V of SD Negeri 0501 Hutanopan. Data collection techniques in this research were obtained through observation, written tests and documentation. The data analysis technique in this research is a qualitative data analysis technique. Based on the results of the research carried out by the author, it can be concluded that the speaking skills of Class V Students of SD Negeri 0501 Hutanopan are low, with only 9 students or 31.03% whose speaking skills are good, while 20 students or 68.97% whose speaking skills are not good. Therefore, researchers try to apply the sociodrama learning model, with the hope that students' speaking skills can be better. Improving students' speaking skills through the sociodrama method for class V of SD Negeri 0501 Hutanopan while in cycle I, the results of observations of students' speaking skills have begun to increase, namely 20 students have 68.97% good speaking skills, while the remaining 9 students have 31 or 31.03% more skills. their speaking skills are not good, and the speaking skills of cycle II students with the application of the sociodrama learning model are 27 students or 93.10% whose speaking skills are good, while the remaining 2 students or 6.90% of their speaking skills are not good, it can be concluded that with the learning model Sociodrama can improve the speaking skills of fifth grade students at SD Negeri 0501 Hutanopan.